Тurkic-arabic language contacts: turkisms in the medieval lexicographical sources - Zhubatova, Б.Н.; Aubakirova, K.K. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2019)
This article discusses the Turkic-Arabic cultural and linguistic contacts under the Mamluk power (XIII-XV centuries) on the basis of medieval Arabic and Turkic-Kipchak written monuments. And also, as an ethnolinguistic source through the analysis of written monuments in the Mamluk-Kipchak language were identified turkisms in Arabic. The influence of the Turkic language on the Arabic language has increased as a result of centuriesold Turkic-Arabic historical and cultural ties. In the era of the Mamluks, diverse relations between the MamluksKipchaks and local peoples, as well as the Golden Horde and Egypt led to the emergence of borrowed words in the Turkic and Arabic languages, as well as in the dialects of the two languages. Turkic words in Arabic, which are found in sources written under the Mamluk government, not only complement a number of historical terms, but are still used in dialects and in the spoken language of Arabic countries. This shows the trace of the Turkic language and steppe culture in the spiritual life of the local people.